2000
DOI: 10.1212/wnl.55.4.565
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of cultured human neuronal cells for patients with stroke

Abstract: Transplantation of cultured neuronal cells is safe in animal models and improves motor and cognitive deficits in rats with stroke. The authors studied the safety and feasibility of human neuronal cellular transplantation in patients with basal ganglia stroke and fixed motor deficits, including 12 patients (aged 44 to 75 years) with an infarct 6 months to 6 years previously (stable for at least 2 months). Serial evaluations (12 to 18 months) showed no adverse cell-related serologic or imaging-defined effects. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
339
2
18

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 584 publications
(364 citation statements)
references
References 11 publications
5
339
2
18
Order By: Relevance
“…These data strongly suggest that neovascularization is essential for neuronal regeneration after stroke and that therapeutic neovascularization is a potentially effective means of enhancing functional recovery. Our observations might explain the mild therapeutic effect achieved by neuronal cell transplantation after stroke reported in humans (38). This leads to the hypothesis that therapeutic neovascularization may be required to achieve optimal "take" of transplanted neuronal precursors in the setting of ischemia.…”
Section: Discussionsupporting
confidence: 52%
“…These data strongly suggest that neovascularization is essential for neuronal regeneration after stroke and that therapeutic neovascularization is a potentially effective means of enhancing functional recovery. Our observations might explain the mild therapeutic effect achieved by neuronal cell transplantation after stroke reported in humans (38). This leads to the hypothesis that therapeutic neovascularization may be required to achieve optimal "take" of transplanted neuronal precursors in the setting of ischemia.…”
Section: Discussionsupporting
confidence: 52%
“…It has been reported that transplantation of other cell sources such as rodent embryonic hippocampal formation cells (37,39), MHP36, a conditionally immortal neuroepithelial stem cell line derived from embryonic mouse (53), and human neuroteratocarcinomaderived neurons (7,50,28) ameliorated neurological deficits induced by brain ischemia. Here we demonstrated that human bone marrow mesenchymal stem cells could engraft and reduce neurological deficits in a rat model of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…In most cases some index of behavioral function has been improved. hNT cells have also been used in clinical trials, and preliminary observations suggest that cell transplantation may be a viable stroke therapy (2,13).…”
mentioning
confidence: 99%